Personality As Correlates Of Paternal Postnatal Depression - Lea Andy Shintya (Fakultas Keperawatan, Universitas Klabat, 2019)
During pregnancy and birth, for mother and newborn baby are the focuses of attention. Many times fathers are left out. This study aimed to determine if personality correlates to paternal postnatal depression. The study used descriptive correlational design, where in data from 177 respondents gathered through purposive sampling. Personality in term of extraversion and neuroticism were significantly related to paternal postnatal depression. Neuroticism was positively correlated to paternal postnatal depression but agreeableness, conscientiousness, openness were not significantly correlated to paternal postnatal depression. This implies that those fathers who scored high in extraversion have low tendency to experience paternal postnatal depression. However, the higher the score in neuroticism the higher in the tendency to experience paternal postnatal depression. From result of this study, researcher have recommendations for nurse educator should emphasize to the future nurse and to the professional nurse that fathers experiences postnatal depression like mothers. When giving health teaching both in the community and in the hospital, nurse educator should consider discussing the topic of postnatal depression. They too should encourage the husbands or fathers to attend the health education activity. Another study can be done comparing the postnatal depression experience by the wife and husband. Keywords: Paternal, Personality,Postnatal depression